News Content And Journalists’ Socialization With Power In Nigeria - Aliagan, Isiaka Zubair (2019)
The news content has always been dependent on its subject or sources. Thus, what constitutes news and how it is sourced have been subject of enquiry in newspaper journalism studies. However, what is seldom done is the probe of the news content and how it is influenced by socialization between the journalist and the power elite that shape the journalist’s news subject and how it is sourced. Therefore, based on this epistemological gap, this study examined the interplay of influence of ownership, medium’s interest, journalist-news source relationship, politics, social relations, and power structures of the society in content sourcing and design by Nigerian newspapers. Premised on political economy of the newspaper and hegemony, the study adopted the mixed methods, comprising quantitative content analysis of 336 editions of two Nigerian newspapers (Daily Trust and The Punch) covering 8871 news stories and in-depth interviews with 20 purposely selected editors and senior journalists to generate its data. In its analysis and presentation of data, the study adopted narrative analysis, complemented with library data. The presentation of findings and discussions are spread across six themes in six chapters. The findings are anchored on the five layers of influence on news content as generated by the study, namely (a) Internal/organization influence (b) individual journalist influence (c) journalist/news source influence (d) ownership influence (e) external/environmental influence.